Linking spatial and social mobility: Is London's "escalator" as strong as it was?. Issue 7 (30th December 2019) - Champion, Tony; Gordon, Ian
Abstract: The "escalator region" concept became a key element of migration literature after Fielding's work on South East England and fuelled a welcome growth of interest in the links between spatial and social mobility. More recent research has shown that London has continued to perform an escalator function since the 1970s, but little attention has been given to how its strength has altered both over time and compared with other parts of the UK. Against the background of the declining rates of internal migration observed in the United States and several other countries, this paper seeks to identify whether London's escalator role was waxing or waning over the four intercensal decades between 1971 and 2011. The primary emphasis is on the chances of people shifting up from noncore to core white‐collar work during each decade for London's nonmigrant and in‐migrant populations, in both absolute terms and relative to England's second‐order cities. It is found that over the three decades since the 1970s London's escalator was still performing in the way originally conceived, but although its net gain of young adults from the rest of England and Wales steadily increased over this period, it was not operating as strongly in 2001–2011 as during the 1990s in terms of both the career‐progression premium gained by its in‐migrants and the extent of its advantage over England's second‐order cities.